Calcium Decay Ability of Extracts Chromolaena odorata L. Leaves (Asteraceae) on Kidney Stones - Dimas Danang Indriatmoko; Maulani Maulani; Tarso Rudiana (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: Kidney stones are one of the causes of chronic and acute kidney failure symptoms. The flavonoid compounds in Chromolaena odorata leave extract are thought to dissolve calcium in kidney stones.  Objective: This study aims to determine the activity of Chromolaena odorata leaves extract as a laxative for calcium kidney stones and to characterize the active extract with a liquid chromatograph mass spectrometry. Methods: The leaves of Chromolaena odorata were extracted by ultrasonication method using 3 solvents in stages, namely n-hexane, ethyl acetate, and methanol. The powder for kidney stones was immersed in an extract solution of n-hexane, ethyl acetate, and methanol for 5 hours at 37° C. The reaction results were analyzed for their absorbance using a UV-Vis spectrophotometer. The fraction with the best activity was analyzed for phytochemical content with various typical reagents and LCMS. Results: Methanol extract of Chromolaena odorata has a better effect in dissolving calcium kidney stones. Methanol extract of Chromolaena odorata can reduce calcium in kidney stones with an EC50 value of 16801 µg/mL. Based on phytochemical tests and LCMS analysis, the methanol extract of Chromolaena odorata leaves contains compounds of the tannins, alkaloids, flavonoids, and steroids. Chromatogram at a retention time of 7.76; 8.96; and 10.01 in the methanol extract of Chromolaena odorata identified 3,5,7,4'-tetrahydroxy-8,3'-dimethoxyflavone; 5,7,4'-trihydroxy-3',5'-dimethoxyflavone, and 5,6,7,8,4'-pentamethoxyflavone compounds. Conclusion: Methanol extract had the best calcium decay activity in kidney stones with an EC50 value of 16801 µg/mL. 3,5,7,4'-tetrahydroxy-8,3'-dimethoxyflavone; 5,7,4'-trihydroxy-3',5'-dimethoxyflavone, and 5,6,7,8,4'-pentamethoxyflavone compounds are contained in methanol extract which is thought to play a role in shedding calcium in kidney stones.